Effect of acute ruminal acidosis on riboflavin and niacin concentrations in sheep - Abdullah Başoğlu; Kürşat Turgut; Mursayettin Eksen; Bünyamin Traş; Mehmet Maden; Mahmut Ok; A. Levent Baş; Tufan Keçeci (Eurasian Journal of Veterinary Sciences)
Six non-lactating, non-pregnant adult ewes divided info two groups of 3 animals each as a control and experimental groups were used to evaluate the effect of experimentally induced acute ruminal acidosis on plasma and rumen fluid riboflavin and niacin concentrations. Decreasements in ruminal fluid pH, the count of protozoa and increase in the count of bacteria were related to gradual decreases in plasma riboflavin and niacin concentration. Plasma riboflavin and niacin concentrations decreased respectively from 9.51 mcg/ml and 7.01 mcg/ml to 0.42 mcg/ml and 0.09 mcg/ml at the first day of the experiment (p<0. 05) and than inclined towards normal values. Similar drastical decrease in the niacin concentration of rumen fluid was determined at the first day of the experiment.